An Insider Perspective on a Research Study Entitled: How Black Men Who Have Sex with Men (BMSM) Learn to Cope with Homophobia and Racism - Lawrence Bryant (Adult Education Research Conference, 2010)
Being an insider in conducting qualitative research (interviews) is oftentimes more multifaceted and complex than usually recognized. However, many researchers agree that this positionality has many benefits. One such benefit is greater insight and awareness not afforded to outsiders.